The Effectiveness of Using Dialogue and Prose Passage Techniques Improving Speaking Ability of The Students at Muhammadiyyah University Tangerang - Destiani Rahmawati (Bandar Lampung University (UBL), 2013)
The researcher realizes that speaking ability is difficult to be achieved because it depends on many factors. Sometimes, the student speaks English because the teacher tells them to speak and to get good marks, but they communicate outside the classroom with their mother tongue. , It can be stated that there are only a few students who have ability in speaking English. The problem of this research are: (1) is there an effect of the use of dialogue on the students’ speaking ability in Muhammadiyah University Tangerang, (2) is there an effect of the use of prose passage on the students speaking ability in Muhammadiyah University Tangerang, (3) is the use of teaching speaking through dialogue more effective than the use of teaching speaking through prose passage.Based on the identification of the problem above, the objectives of this study are to investigate: a. There is an effect of the use of dialogue on the students’ speaking ability, b. There is an effect of the use of prose passage on the students` speaking ability, c. The use of teaching speaking through dialogue is more effective than the use of teaching speaking through prose passage In this research, the instrument of collecting data was speaking test by an open interview. An interview is used to measure how far the students’ ability in speaking English. The researcher used cluster random sampling, thus one group was A.1 selected in the experimentalal groups and the control class was A.2 for control group.The description of data can be seen that mean in experimental class (A.1) was 75.25. It means that the mean is higher than the mean in control class (A.2) was 69.50. The minimum scores in experimental class were 55, and the minimum scores in control class is 50. The maximum scores in experimental class were 90, and the maximum scores in control class were 85. The ranges of the scores were 35 point. The median in experimental class (A.1) was 75, and the control class (A.2) was 70. The mode of the data in experimental class (A.1) was 75, and the control class (A.2) was 70.Based on data analysis and comparison of the result of the pre-test and the post-test in experimental class (A.1) and control class (A.2), it was found that: (1) there was an effect of the use of dialogue on the students’ speaking ability in Muhammadiyah University Tangerang rang, (2) there was an effect of the use of prose passage on the students speaking ability in Muhammadiyah University Tangerang (3) the use of teaching speaking through dialogue is more effective than the use of teaching speaking through prose passage. The writer puts forward some suggestions that might be useful for any teacher who teaches English as a foreign language. The lecturer should present dialogue activities by giving clear instruction to the students in order to help them in implementing it. Secondly, to eliminate boring situation, the lecturer should take the dialogue for appropriate level of the students. Next, the lecturer had better not to be involved in the role dialogue activities but the lecturer should just guide and control them. Finally, The lecturer should choose the appropriate approach, method, and techniques in speaking.The result of this research is expected to be beneficial for all English lecturers who teach in the speaking class. The result showed that both dialogue and prose passage were important in students speaking ability. However, introducing the topic and chose a suitable speaking material preferable to make the students’. Becoming aware of their speaking ability in comprehend of the speaking ability through dialogue and prose passage, this research was hoped to be as the bases of the reader to identify their most appropriate technique based on their own speaking ability.